PROFIL PEMAHAMAN KONSEP TEOREMA PYTHAGORAS SISWA BERDASARKAN PERBEDAAN GAYA KOGNITIF FIELD INDEPENDENT DAN FIELD - Nurafni Nurafni; Asih Miatun; Hikmatul Khusna (KALAMATIKA Jurnal Pendidikan Matematika, 2018)
This research is a descriptive qualitative approach which aims to describe profile of understanding of pythagoras theorem concept of students based on the difference of field independent and dependent cognitive style. The subjects of this study are 9th grade students of junior secondary school. Subject determination is done using GEFT instrument and mathematics teacher’s consultation, then continued by giving concept comprehension test on Pythagorean theorem material and interview. Checking the validity of data is done by time’s triangulation. The results showed that student: 1) states the meaning of Pythagoras's theorem given in his own language by noting Pythagorean theorem’s definition; 2) when using the concepts of Pythagoras theorem, students use triangle images as representations to facilitate an interpretation of given sides position. Then the students find the unknown values and use Pythagoras theorem to solve the problem; 3) using the necessary condition or sufficient condition of a concept to determine the area of a triangle using Pythagorean theorem by finding a side. While, the results for field independent cognitive style are student: 1) expresses the meaning of Pythagoras theorem by using their own language and mentioning the symbols; 2) using the concepts of Pythagorean theorem to solve the problem given by using multiplication operations to determine one of unknown sides. Then, student use pythagoras theorem to find the answer of the given problem; 3) using the necessary conditions or sufficient terms a concept of Pythagoras theorem by stating that it must be known two sides or not.